2004
DOI: 10.1002/qua.20132
|View full text |Cite
|
Sign up to set email alerts
|

DFT studies on key intermediates in thiamin catalysis

Abstract: ABSTRACT:The diphosphate ester (ThDP) of thiamin (vitamin B 1 ) is an important cofactor of enzymes within the carbohydrate metabolism. From experiments of site-specific variants and nuclear magnetic resonance (NMR) studies, it is known that the protonation of the N1Ј atom is a significant step in the coenzyme activation by the enzymatic environment. Therefore, we have performed density functional theory (DFT) calculations on the B3LYP/ 6-31G* level of N1ЈH and N1ЈCH 3 thiamin as model systems to study the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…For example, in some very early work, Jordan used semi-empirical methods to study the electronic structure and conformational space of the cofactor in the gas phase, acknowledging the difficulty of comparing these results to reactions in solution and on the enzyme [1920]. Thirty years later, density functional theory (DFT) calculations showed that the 4′-amino moiety of the cofactor can either accept or donate a proton in the reactions, depending on the protonation state of N1′ [21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in some very early work, Jordan used semi-empirical methods to study the electronic structure and conformational space of the cofactor in the gas phase, acknowledging the difficulty of comparing these results to reactions in solution and on the enzyme [1920]. Thirty years later, density functional theory (DFT) calculations showed that the 4′-amino moiety of the cofactor can either accept or donate a proton in the reactions, depending on the protonation state of N1′ [21].…”
Section: Introductionmentioning
confidence: 99%
“…The adopted methodology, called the cluster approach, has been very successful in elucidating reaction mechanisms of a wide variety of enzymes (Siegbahn and Himo, 2009 , 2011 ; Siegbahn and Blomberg, 2010 ; Blomberg et al, 2014 ; Himo, 2017 ). A number of previous theoretical studies using a variety of computational techniques have considered aspects of mechanism of a number of ThDP-dependent enzymes (Friedemann et al, 2004 ; Lie et al, 2005 ; Wang et al, 2005 ; Jaña et al, 2010 ; Topal et al, 2010 ; Xiong et al, 2010 ; Paramasivam et al, 2011 ; Alvarado et al, 2012 ; Hou et al, 2012 ; Jaña and Delgado, 2013 ; Sheng and Liu, 2013 ; Sheng et al, 2013 , 2014 ; Sánchez et al, 2014 ; Zhang et al, 2014 ; Zhu and Liu, 2014 ; Lizana et al, 2015 ; Nauton et al, 2016 ; White et al, 2016 ). Relevant results from these studies have been incorporated into the discussion of the BFDC mechanism below.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental [30] and theoretical studies [31][32][33][34][35] have been aimed at understanding the mechanism of the reaction and the structures of the intermediates associated with the reaction. The first step of the pathway can be written as Pyruvic acid þ CoA þ ferredoxin ðoxÞ $ acetyl-CoA þ CO 2 þ ferredoxin ðredÞ ð 1Þ…”
Section: Introductionmentioning
confidence: 99%
“…The intermediate (C) undergoes an internal proton transfer via a barrier (D, TS2) to form 2-lactyl ThDP (E, LThDP).Decarboxylation of LThDP occurs through a transition state (F, TS3) to form a stable enamine and CO 2 (G). Detailed experimental studies have been published that delineate the complete decarboxylation process of pyruvate dehydrogenases (PDH), pyruvate decarboxylases (PDC) and pyruvate oxidases (POX) by various research groups[2,30,34,60,[66][67][68][69][70].…”
mentioning
confidence: 99%